Correction: Alternative strategies for mosquito-borne arbovirus control. - Nicole L Achee; John P Grieco; Hassan Vatandoost; Gonçalo Seixas; Joao Pinto; Lee Ching-Ng; Ademir J Martins; Waraporn Juntarajumnong; Vincent Corbel; Clement Gouagna; Jean-Philippe David; James G Logan; et al. (Public Library of Science (PLoS), 2019)
[This corrects the article DOI: 10.1371/journal.pntd.0006822.].